The perception of athlete towards parental support and pressure / Wan Muhammad Zulhusmi Wan Mustaffa - Wan Mustaffa, Wan Muhammad Zulhusmi (Faculty of Sport Science and Recreation, 2017)
The purpose of this study was to identify the perception of athlete towards parental support and pressure. A total of eighty-one athlete (N=81) was involved via random sampling in this study. The method of this study were descriptive and using intrumentations of demographic questionnaire and the athlete questionnaire (support and pressure). Based on the discriptive statistics showed that the parental support scale are from 1.40 - 2.23 for the average of mother's total support which is 'never' and 'rarely' support. For father's mean in average support is from 1.69 - 2.38. The result also shown the relationship between parent involvement in athletes' sport and their support for mother, (p = 0.05, r = 0.22) and (p = 0.000, r = 0.58) for father. The result also show the relation between parental pressure and parental involvement in athletes' sport participation which is it shown a significant (p = 0.002, r = 0.34) for mother and (p = 0.000, r = 0.42) for father which is both has positive relation.